2016
DOI: 10.1111/ger.12220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of a chamomile (Matricaria chamomilla) and linseed (Linum usitatissimum) saliva substitute in the relief of xerostomia in elders

Abstract: New chamomile- and linseed-based saliva substitute was effective in relieving xerostomia symptoms in older participants of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
0
15
0
4
Order By: Relevance
“…The flow chart for inclusions is presented in Figure 1. The search included 42 articles, published between 1979 and 2017 (Aliko, Alushi, Tafaj, & Isufi, 2012; Alpöz et al, 2015; Alpöz et al, 2008; Alves, Motta, Messina, & Migliari, 2004; Andersson et al, 1995; Apperley, Medlicott, Rich, Hanning, & Huckabee, 2017; Blixt‐Johansen et al, 1992; Bots et al, 2005; Dalodom et al, 2016; Davies & Singer, 1994; Dirix, Nuyts, Vander Poorten, Delaere, & Van den Bogaert, 2007; Donath, Tonner, Chavda, Gatignol, & Bouyrie, 2016; Duxbury, Thakker, & Wastell, 1989; Epstein, Emerton, Le, & Stevenson‐Moore, 1999; Frost, Shirlaw, Walter, & Challacombe, 2002; Furumoto, Barker, Carter‐Hanson, & Barker, 1998; Gil‐Montoya, Subirá, Ramón, & González‐Moles, 2008; Heydarirad, Rezaeizadeh, Choopani, Mosavat, & Ameri, 2017; Jellema et al, 2001; Johansson, Andersson, Attström, Glantz, & Larsson, 1994; Klestov et al, 1981; Matear & Barbaro, 2005; McMillan, Tsang, Wong, & Kam, 2006; Momm, Volegova‐Neher, Schulte‐Mönting, & Guttenberger, 2005; Morales‐Bozo et al, 2017; Mouly, Orler, et al, 2007; Mouly, Salom, et al, 2007; Nakamoto, 1979; Oh, Lee, Kim, & Kho, 2008; Regelink, Vissink, Reintsema, & Nauta, 1998; Rogus‐Pulia, Gangnon, Kind, Connor, & Asthana, 2018; Salom et al, 2015; Shahdad, Taylor, Barclay, Steen, & Preshaw, 2005; Silvestre, Minguez, & Suñe‐Negre, 2009; Skrinjar et al, 2015; Stewart et al, 1998; Sweeney, Bagg, Baxter, & Aitchison, 1997; Temmel, Quint, Schickinger‐Fischer, & Hummel, 2005; van der Reijden, van der Kwaak, Vissink, Veerman, & Amerongen, 1996; Visch, Gravenmade, Schaub, Van Putten, & Vissink, 1986; Vissink et al, 1983).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow chart for inclusions is presented in Figure 1. The search included 42 articles, published between 1979 and 2017 (Aliko, Alushi, Tafaj, & Isufi, 2012; Alpöz et al, 2015; Alpöz et al, 2008; Alves, Motta, Messina, & Migliari, 2004; Andersson et al, 1995; Apperley, Medlicott, Rich, Hanning, & Huckabee, 2017; Blixt‐Johansen et al, 1992; Bots et al, 2005; Dalodom et al, 2016; Davies & Singer, 1994; Dirix, Nuyts, Vander Poorten, Delaere, & Van den Bogaert, 2007; Donath, Tonner, Chavda, Gatignol, & Bouyrie, 2016; Duxbury, Thakker, & Wastell, 1989; Epstein, Emerton, Le, & Stevenson‐Moore, 1999; Frost, Shirlaw, Walter, & Challacombe, 2002; Furumoto, Barker, Carter‐Hanson, & Barker, 1998; Gil‐Montoya, Subirá, Ramón, & González‐Moles, 2008; Heydarirad, Rezaeizadeh, Choopani, Mosavat, & Ameri, 2017; Jellema et al, 2001; Johansson, Andersson, Attström, Glantz, & Larsson, 1994; Klestov et al, 1981; Matear & Barbaro, 2005; McMillan, Tsang, Wong, & Kam, 2006; Momm, Volegova‐Neher, Schulte‐Mönting, & Guttenberger, 2005; Morales‐Bozo et al, 2017; Mouly, Orler, et al, 2007; Mouly, Salom, et al, 2007; Nakamoto, 1979; Oh, Lee, Kim, & Kho, 2008; Regelink, Vissink, Reintsema, & Nauta, 1998; Rogus‐Pulia, Gangnon, Kind, Connor, & Asthana, 2018; Salom et al, 2015; Shahdad, Taylor, Barclay, Steen, & Preshaw, 2005; Silvestre, Minguez, & Suñe‐Negre, 2009; Skrinjar et al, 2015; Stewart et al, 1998; Sweeney, Bagg, Baxter, & Aitchison, 1997; Temmel, Quint, Schickinger‐Fischer, & Hummel, 2005; van der Reijden, van der Kwaak, Vissink, Veerman, & Amerongen, 1996; Visch, Gravenmade, Schaub, Van Putten, & Vissink, 1986; Vissink et al, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…In one observation report, the staff of an establishment for elderlies measured meal duration, reported the residents' pain complaints and subjectively assessed their ability to speak, eat and swallow (Blixt‐Johansen et al, 1992). Sixteen studies globally measured the impact of xerostomia using validated (Apperley et al, 2017; Bots et al, 2005; McMillan et al, 2006; Morales‐Bozo et al, 2017), or non validated (Alves et al, 2004; Andersson et al, 1995; Frost et al, 2002; Furumoto et al, 1998; Gil‐Montoya et al, 2008; Klestov et al, 1981; Momm et al, 2005; Mouly, Orler, et al, 2007; Mouly, Salom, et al, 2007; Oh et al, 2008; Shahdad et al, 2005; Sweeney et al, 1997) comprehensive questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…The use of medicinal herbs and herbal medicines is an age-old tradition, and the recent progress in modern therapeutics has stimulated the use of natural products worldwide for diverse ailments and diseases ( 1 – 10 ). Matricaria recutita chamomilla of the Asteraceae family is an annual plant indigenous to Europe and Asia ( 11 ), possessing branched, erect, and smooth stems ( 12 , 13 ). Its other names are chamomile or camomile, Italian camomilla, German chamomile, wild chamomile, Hungarian chamomile, ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained following treatment with the herbal mouthwash are in agreement with previous reports, describing the capability of several active herbal ingredients, to reduce the sensation of pain, and increase saliva secretion. For instance, in a randomized study of elderly patients, chamomile was shown to provide relief from xerostomia symptoms, such as the sensation of oral dryness, a burning tongue, and difficulty swallowing [8].…”
Section: Discussionmentioning
confidence: 99%